2013
DOI: 10.1097/sla.0b013e3182774522
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Global Gastrointestinal Motility After Sleeve Gastrectomy

Abstract: SG accelerates gastric emptying and small bowel transit of semisolids. In addition, it delays the initiation of cecal filling and T ICVt. This early and prolonged contact of food with the distal small bowel mucosa may explain the metabolic effects of SG occurring before substantial weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 48 publications
3
78
1
7
Order By: Relevance
“…The rapid gastric emptying after LSG [30,31] could result in accelerated entry of carbohydrates into the small intestine with rapid glucose absorption prompting rapid and marked insulin secretion [32]. However, in our study, we did not find differences between the HYPO and EU subjects in the glucose levels at 30′, peak glucose (data not shown), and glucose AUC (0-30) levels, suggesting that glucose absorption was comparable in these groups.…”
Section: Discussioncontrasting
confidence: 76%
“…The rapid gastric emptying after LSG [30,31] could result in accelerated entry of carbohydrates into the small intestine with rapid glucose absorption prompting rapid and marked insulin secretion [32]. However, in our study, we did not find differences between the HYPO and EU subjects in the glucose levels at 30′, peak glucose (data not shown), and glucose AUC (0-30) levels, suggesting that glucose absorption was comparable in these groups.…”
Section: Discussioncontrasting
confidence: 76%
“…First, marked reductions in ghrelin levels occur after complete removal of the gastric fundus, which is the site of the production of the hormone ghrelin, and such reduction would aid weight loss [37]. Second, quick elevations of the postmeal GLP-1 and PYY responses are induced by the rapid bowel transit time that occurs following after, and these factors might aid weight reduction and metabolic control [23,38]. However, a recent study in mice by Ryan et al showed that neither ghrelin nor GLP-1 plays an essential role in LSG.…”
Section: Discussionmentioning
confidence: 98%
“…The sleeve itself remained without recognizable peristalsis or showed only uncoordinated or passive motion [16]. In 2012, Melissas et al [17] showed not only accelerated gastric emptying but also faster small bowel transit of semisolids. This early and prolonged contact of food with the distal small bowel mucosa may explain the metabolic effects of LSG occurring before substantial weight loss.…”
Section: Mechanismsmentioning
confidence: 99%